Pengaruh Kompensasi Dan Motivasi Terhadap Kinerja Karyawan CV Glagah Arjuna Broom Purbalingga - Abdul Latief, Zulfikar (DFAME Digital Financial Accounting Management Economics Journal, 2024)
The problems at CV Glagah Arjuna Broom Purbalingga are minimal compensation and lack of work enthusiasm which indicates a lack of motivation so that employee performance is not optimal, so the aim of this research is to determine the effect of compensation and work motivation on employee performance at CV Glagah Arjuna Broom Purbalingga. This type of research uses quantitative methods. The testing in this research uses technique non-probability sampling using a saturated sample where all employees were used as research samples, namely 33 employees. Tests carried out with software SPSS 26. The conclusion in this research is that partial compensation has no effect on employee performance, partial work motivation has a positive and significant effect on employee performance, but compensation and work motivation simultaneously have an effect on employee performance. The coefficient of determination value is 73%, meaning that employee performance variables can be explained by independent variables and the remaining 27% is influenced by other variables that are not included in this research. So it would be better for management to review compensation and make more efforts to improve employee performance so that performance can be optimal.